The Role of Green Platform Design in Enhancing User Comfort in Digital Marketplaces - Harun Adama Sume; Randy Hermawan; Aditya Rifandy Zaenudin; Herman S. Soegoto; Lilis Puspitawati (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the role of green platform design in enhancing user comfort within digital marketplace environments by exploring how sustainability-oriented interface elements influence user experiences and behaviors.Research Methodology: This study employed a qualitative descriptive approach. Data were collected through in-depth interviews, direct observations, documentation, and open-ended questionnaires involving 93 users of Shopee, Tokopedia, and TikTok Shop. The collected data were analyzed using thematic analysis to identify key patterns related to green platform design and user comfort.Results: The findings indicate that green platform design elements, including simplified interface layouts, intuitive navigation, eco-friendly features, sustainability-related product information, eco-labels, and green product recommendation systems, contribute to higher user comfort, improved search efficiency, increased trust, and enhanced overall satisfaction.Conclusions: The study concludes that green platform design serves as an important factor in shaping positive user experiences in digital marketplaces. Integrating sustainability principles into platform interfaces not only supports environmental awareness but also strengthens user engagement and marketplace competitiveness.Limitations: This study is limited by its qualitative approach and the involvement of users from three selected digital marketplaces, which may restrict the generalizability of the findings to broader e-commerce contexts.Contributions: This study highlights green platform design as a determinant of user comfort and provides practical insights for developing sustainable digital marketplace strategies that enhance user experience and loyalty.